Sistem Penggajian Berorientasi Ijarah - Mohammad Arifin (Universitas Muhammadiyah Surabaya, 2021)
What is meant by the implementation of the ijarah principle in the payroll system is a study of the analysis of the existing theory to determine a payroll system with a work agreement in accordance with the ijarah principle or sharia economic law. A job carried out by an entrepreneur or company and an institution that cooperates or employs a worker or employee must of course remain within the corridor of sharia economic law by conducting ijarah contract transactions whose objects and forms of work are required in accordance with the recommendations of the Qur'an and Al-Hadith.